2021
DOI: 10.3390/ijerph182111257
|View full text |Cite
|
Sign up to set email alerts
|

Forefoot Deformities in Patients with Rheumatoid Arthritis: Mid- to Long-Term Result of Joint-Preserving Surgery in Comparison with Resection Arthroplasty

Abstract: Background: Joint-preserving surgery for the forefoot has been increasingly performed for rheumatoid arthritis (RA). We compared joint-preserving surgeries with resection arthroplasty for RA in the forefoot. Methods: Forefoot surgeries were performed on 62 toes in 42 patients with RA (men: 2; women: 40) between 2002 and 2018. Three groups were compared: PP—31 toes treated with joint-preserving surgery involving the modified Mann method for the big toe and offset osteotomy for lesser toes, PR—15 toes treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…3 Among the myriad afflictions RA imposes, foot deformities rank prominently, with an estimated 90% of RA patients experiencing some form of foot deformity and a notable 25%-40% undergoing surgery to address forefoot complications. 3 Previous studies demonstrated that the instability of the first tarsometatarsal (TMT) joint can be related to HV deformity, and the presence of the instability may be predictable by assessing the articular facet of the medial cuneiform in plain anteroposterior X-rays. [4][5][6][7][8][9][10][11] Surgical correction of HV includes various procedures, with joint-preserving techniques becoming more prevalent due to advancements in RA treatment.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…3 Among the myriad afflictions RA imposes, foot deformities rank prominently, with an estimated 90% of RA patients experiencing some form of foot deformity and a notable 25%-40% undergoing surgery to address forefoot complications. 3 Previous studies demonstrated that the instability of the first tarsometatarsal (TMT) joint can be related to HV deformity, and the presence of the instability may be predictable by assessing the articular facet of the medial cuneiform in plain anteroposterior X-rays. [4][5][6][7][8][9][10][11] Surgical correction of HV includes various procedures, with joint-preserving techniques becoming more prevalent due to advancements in RA treatment.…”
mentioning
confidence: 99%
“…18 The recurrence of HV was defined as hallux valgus angle (HVA) ≥20° after surgery. 3,19 The morphology of the TMT articular facet of the medial cuneiform was assessed by first TMT joint angle (1TMTJA) proposed by Brage et al (Figure S1). 9 The hindfoot deformity, reported as a risk factor for HV recurrence, 20,21 was assessed by talonavicular coverage angle (TNCA), lateral talocalcaneal angle (LTCA), calcaneal pitch angle (CPA), and talus-M1 angle (T1MTA).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Takakubo et al [ 6 ] compared joint-preserving surgery with joint-sacrificial surgery in patients with RA. In this study, joint-sacrificing surgery was performed if severe subluxation and dislocation of the MTP joint with contractures and stiffness were observed on the manipulation or stress radiographs.…”
mentioning
confidence: 99%